Learning Strategy for Jambi Regional Musical Arts in Local Content Subjects in Class VII - Voltra, Jontra; Narayan, Swasti; Nayasi, Kasanita (Program Magister Teknologi Pendidikan Universitas Jambi, 2022)
The research focused on the implementation of teaching strategies for Jambi traditional music in local content subjects at Public Middle School 23 Merangin. It employed a qualitative phenomenological approach, involving interviews, observations, documentation, and questionnaires. The planning stage involved mapping the curriculum and developing a teaching plan based on chosen themes. During implementation, various teaching strategies like social inquiry and problem-based learning were utilized alongside multimedia tools. Evaluation included assessing student participation and performance through various methods. The data analysis used in this research is data analysis using a qualitative approach, namely data reduction, data presentation and drawing conclusions. Results showed that the teaching strategies were well-organized and effective, supporting the achievement of learning goals. The significance lies in enhancing cultural values through education. The study's novelty and implications lie in its comprehensive approach to teaching strategies and their impact on learning outcomes. In addition, in-depth analysis of the use of learning media through six dimensions provides more holistic insight in selecting and utilizing appropriate learning media.